Efficacy of the green synthesized nickel-oxide nanoparticles against pulse beetle, Callosobruchus maculatus (F.) in black gram (Vigna mungo L.). Issue 4 (24th September 2021) - Rahman, Md. Anisur; Parvin, Afsona; Khan, Md. Sajibul Haque; War, Abdul Rasheed; Lingaraju, K.; Prasad, Ram; Das, Sudipta; Hussain, Barkat; Bhattacharyya, Atanu
Abstract: Nickel-oxide nanoparticles (NiO NPs) using aqueous Rauvolfia serpentine leaf extract were tested against Callosobruchus maculatus . Synthesis of NiO NPs was confirmed by various physiochemical methods such as UV-visible spectroscopy, powder X-ray diffraction, Fourier transform infrared spectroscopy etc. The sharp and strong reflections (111, 200, 220, 311 and 222 crystal planes) of the monoclinic phase and cubic NiO NPs were observed. The crystallite sizes varied in Scherrer's and W–H plots from 9.42 (20 ml) to 4.89 nm (15 ml) and 20.0 nm (10 ml) to 10.12nm (15 ml), respectively. The highest strain was observed in 15 ml (93.8 × 10 −4 ) and the lowest (37.9 × 10 −4 ) in 20ml extract. The C. maculatus on black gram seeds with 5, 10, 20 and 40ppm NiO NPs showed decreased fecundity and an increased developmental period in a dose-dependent manner. The longevity of the insect did not differ significantly. Seed germination was significantly reduced at 40ppm (79.12%)